Energy and seismic retrofit of historic timber-framed houses in Portugal: Building predictive models in future scenarios - Stellacci, S.; Domingos, L.; Poletti, E. (Atas do 4º Congresso Internacional de História da Construção Luso-Brasileira (4th CIHCLB), 2023)
This research addresses the comparison of building performance before and after implementing energy and seismic retrofitting techniques within simulation models, under the current climate condition vs. predicted environment conditions (2030-2100). It aims to identify a set of feasible interventions within distinct indoor building conditions (number of inhabitants and occupancy schedule) in three design scenarios. To this end, we adopt parametric modelling tools (Rhinoceros, Grasshopper, EnergyPlus) combined with a multicriteria decision analysis (M-MACBETH, Measuring Attractiveness through a Categorical-Based Evaluation Technique). This model is tested in an historic house, a multi-storey overhanging timber-framed house in Lisbon parish, which is representative of valuable traditional construction systems in high seismic hazard zone in the Mediterranean basin. Future studies can address other building simulations evaluated against architectural, structural, environmental, and economic-related parameters. The influence of weighting on the interventions against different criteria can be addressed also considering the uncertainty about the impact of each group of intervention in sensitivity and robustness analyses.